Analisis Pengaruh Hexagon Fraud Model Terhadap Kecurangan Laporan Keuangan pada Perusahaan Sektor Consumer Non-Cyclicals Subindustri Makanan Olahan Periode 2019-2023 - Gunawan, William; Tjandrawan, Denny Iskandar (Ikatan Da'i Indonesia, 2025)
This study analyzes the influence of the Hexagon Fraud Model on financial statement fraud in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange during the period 2019-2023. The study examines six key factors in the model: financial pressure (proxied by company financial stability), perpetrator ability (measured through director turnover), collusion (reflected through company culture), opportunity (measured through the effectiveness of internal control), rationalization (proxied through external auditor turnover), and ego (as a latent variable not directly proxied). This research is motivated by the inconsistency of previous empirical findings regarding the influence of each of these factors on financial statement fraud. Some studies show a positive and significant correlation between financial pressure and fraud, while others find no such relationship. Similarly, the influence of other factors such as monitoring, auditor and director turnover, also shows diverse results. Using a quantitative approach, this study empirically tests the influence of the six factors of the Hexagon Fraud Model on financial statement fraud. Secondary data in the form of company financial statements and data related to good corporate governance will be collected and analyzed using regression analysis. The research results are expected to provide significant empirical contributions to understanding the determinants of financial statement fraud in Indonesia, particularly in the Consumer Non-Cyclicals sector. These findings are expected to have practical implications for regulators, investors, and company management in efforts to prevent and early detect financial statement fraud. Furthermore, this study seeks to fill the knowledge gap and provide a more comprehensive understanding of the complexities of the factors that contribute to financial statement fraud.